2011
DOI: 10.1108/14676371111168287
|View full text |Cite
|
Sign up to set email alerts
|

Cotton and sustainability

Abstract: PurposeThe purpose of this paper is to examine the effect of intensive extra‐curricular learning opportunities on students' knowledge, skills, and attitudes regarding cotton and sustainability.Design/methodology/approachA three‐phase extra‐curricular learning opportunity was designed to include a Sustainable Cotton Summit; pre‐summit and post‐summit surveys of students' knowledge, skills, and attitudes toward cotton; and an individual essay competition.FindingsThe two‐group mean comparisons showed that the sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…Rands’ (2009) principles-attributes matrix (PAM) suggested that successful teaching should impact students’ knowledge, skills and attitudes. In addition, Ha-Brookshire and Norum (2011) indicated that sustainable development, organizational responsibility and personal responsibility should be the key topics while learning about sustainability. Hence, students’ knowledge, skills and attitude toward sustainable development, organizational and personal responsibility were assessed to investigate the overall impact of the study’s learning components.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rands’ (2009) principles-attributes matrix (PAM) suggested that successful teaching should impact students’ knowledge, skills and attitudes. In addition, Ha-Brookshire and Norum (2011) indicated that sustainable development, organizational responsibility and personal responsibility should be the key topics while learning about sustainability. Hence, students’ knowledge, skills and attitude toward sustainable development, organizational and personal responsibility were assessed to investigate the overall impact of the study’s learning components.…”
Section: Methodsmentioning
confidence: 99%
“…Standardized scale developed by Ha-Brookshire and Norum (2011) were used in survey development. Questions were slightly modified to fit the study context.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, detached from the clearly structured and assessment-focused schooling environment, extracurricular education allows to overcome structural boundaries and to implement an advantageous learning format for ESD [56]. With regards to ESD, the positive effect of extracurricular activities on students' knowledge and attitudes regarding sustainability and SD has been recorded in several studies [57][58][59]. Extracurricular activities are likewise perceived by teachers as valuable approach to foster competencies for citizenship, such as decision-making [60].…”
Section: Introductionmentioning
confidence: 99%
“…Although recent studies describe a positive direct relation between purchase attitude and purchase intentions (Chen, 2013;Patrícia-Silva, Figueiredo, Hogg & Sottomayor, 2014;Cheah, Phau & Liang, 2015), this model does not address how the ethnic identity of consumers influences the purchase intention within a context of artisan products. Studies on purchasing behavior consider ethnical identity as a predictor to explain the attitude and purchase intention because it is related to the emotions and attitude of consumers who are proud of their ethnic origins (Ha-Brookshire & Norum, 2011). Therefore, the aim of this study is to analyze how the purchase attitude mediates the relation between ethnic identity and intention to purchase ethnic textiles.…”
Section: Introductionmentioning
confidence: 99%